Механiзм збiльшення iнтенсивностi випромiнювання газорозрядної плазми на сумiшах парiв дийодиду ртутi, ксенону та неону в фiолетово-синьому спектральному дiапазонi - Malinina, A. O.; Shuaibov, O. K.; Malinin, O. M. (Publishing house "Academperiodika", 2018)
A mechanism allowing the intensity of radiation emitted in the blue-violet spectral interval by gas-discharge plasma created in the mixtures of mercury diiodide vapor, xenon, and neon to be increased in comparison with the intensity of radiation from gas-discharge plasma in the mixtures of mercury diiodide vapor and neon is established. The plasma parameters and the reduced electric field, at which the specific discharge power spent for the excitation of mercury monoiodide exciplex molecules is maximum, are determined. The research results can be used for the creation of a more efficient exciplex lamp with bands emitted in the blue-violet spectral interval.